Utilization of personal protective equipment among sanitation workers in faecal-waste management plants in cities in Uganda - Bulafu, Douglas; Ninsiima, Lesley Rose; Tamale, Bridget Nagawa; Baguma, James Natweta; Namakula, Lydia Nabawanuka; Niyongabo, Filimin; Ndejjo, Rawlance; Musoke, David (Frontiers in Environmental Health, 2025)
IntroductionIncreased urbanization in Uganda has exerted pressure on the existing sanitation facilities including sewer systems and fecal-waste treatment plants increasing health, and environmental risks to sanitation workers and the public. Sanitation workers are also exposed to biohazards while working, which poses a great threat to their health. This study assessed utilization of personal protective equipment (PPE) and associated factors among sanitation workers in fecal-waste management plants in Uganda's regional cities.MethodsA cross-sectional study was conducted among 417 sanitation workers in fecal waste treatment plants in nine cities in Uganda. Data were collected using a semi-structured questionnaire uploaded on Kobo collect software and analyzed in Stata version 14 software. ResultsThe majority (95.0%) of the study participants were males, 46.5% were above 30 years and 60.7% consistently utilized PPE in the 30 days prior to the study. Experiencing work-related illness (APR = 0.39,95% CI:0.23–0.66), presence of an occupational health and safety officer (APR = 2.32, 95%CI:1.34–4.02), presence of PPE regulations (APR = 2.85,95%CI:1.50–5.39), and mandatory PPE use at work were significantly associated with consistent PPE use. Discussion/ConclusionConsistent PPE use among sanitation workers at fecal-waste management plants was suboptimal. Hence, fecal-waste management plants should conduct routine training, provide PPE, and employ occupational health officers to enforce and supervise PPE use.